The Study of Geomythology and Cultural Anthropology in Mountain Folklore Sabampolulu and Mountains Nepa-nepa in Kabaena, Southeast Sulawesi - Abdin, Non; Jaelani, Jaelani; Gusli, Suhendro; Ali, La (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the folklore of Mount Sabampolulu and Mount Nepa-nepa on Kabaena Island, Southeast Sulawesi, using a geomythological and cultural anthropological approach to understand the relationship between geological phenomena and the cultural construction of the local community. Through a qualitative-descriptive method involving interviews, field observations, and narrative analysis, the research finds that the myths of the two mountains record collective memories of geological events such as eruptions, erosion, and floods, while also functioning as tools for ecological education, identity formation, and the preservation of cultural values. In conclusion, this folklore serves as a living ecological archive that interconnects myth, history, and the environment within a unified framework of cultural meaning.